ANALISIS TEKNIS DAN EKONOMIS PRODUKSI TERPADU ARANG DAN CUKA KAYU DARI TIGA JENIS KAYU - Tjutju Nurhayati; Sylviani Sylviani; Mahpudin Mahpudin (Pusat Penelitian dan Pengembangan Hasil Hutan, 2003)
Analysis on the integrated production of charcoal and wood vinegarhas been conducted using the raw materials of three wood species, i.e. mangrove (Bruguera sp.), mangium (Acacia mangium), and tusam (Pinus merkusii). As such, those three were each carbonized into charcoal through a direct burning in a dome kiln with 2 m3 capacity; and concurrently, the distillation through the cooling of.the generated gas/vapor fraction was conducted to collect the wood vinegar. The resulting charcoal werefurther treated either with or without purification process. To evaluate the qualities of the two products (i.e. charcoal and wood vinegar), the physico-chemical and economic analyses were examined. Economic analysis covered the collection of data/information on purchasing prices of the equipment. material-procuring cost for the kiln, kiln-erection cost. production cost, cost of procuring auxiliary matters, charcoal and wood vinegar prices, and others, followed by their assessment. Results of the analysis were as follows:Integrated production of charcoal and the one of wood vinegar turned out to be the best with respect to their technical aspects and physico-chemical properties was from the raw material of mangrove wood species. In this regard, the yield of charcoal and wood vinegar was the highest. Likewise, the qualities of the charcoal could correspond to usage standard of charcoal for iron ore. Also, the qualities of the wood vinegar could meet the Japan Standard Requirement.The implementation of purification treatment on the resulting charcoal could decrease the volatile matter content, and increase fixed carbon content and calorific value without affecting the production of wood vinegar. As such, the volatile matter contents in mangium charcoal decreased from 27.09 percent to 17.35 percent, and in tusam charcoal from 33.18 percent to 24. 79 percent.Productions of charcoal and wood vinegar for one m3 of wood were in the range of 181- 217 kg and 169 - 205 kg, respectively for mangrove wood; 110 -121 kg and 121 - 125 kg, respectively formangium wood; and 111-121 kg and 141 kg, respectively for tusam wood.Production of charcoal which is in integration with the one of wood vinegar can gain a significant benefit. Such benefit can be achieved after 5 years of wood vinegar production, i.e. 82.6 percent per year from mangrove wood, and mangium as well as tusam wood. Conversely, the production of wood vinegar in integration with the one of charcoal can gain additional benefit, i.e. 39.7 percent per year from mangrove wood, and 39.9 percent per-year from mangium as well-as-tusam wood. The benefit per year of such integrated production in the sixth year will be even greater, since the interest payment and loan can be ultimately fulfilled. All the investment of the factory with implements an integrated production-of charcoal and wood vinegar can be returned in one year and 3 months.